Contingency management for behavior change: Applications to promote brief smoking cessation among opioid-maintained patients - Dunn, Kelly E. (2011)
Cigarette smoking is highly prevalent among patients who are being treated for opioid-dependence, yet there have been limited scientific efforts to promote smoking cessation in this population. Contingency management (CM) is a behavioral treatment that provides monetary incentives (available in the form of vouchers) contingent upon biochemical evidence of drug abstinence. This paper discusses the results of two studies that utilized CM to promote brief smoking cessation among opioid-maintained patients. Participants in a pilot study were randomly assigned for a 2-week period to a Contingent group that earned monetary vouchers for providing biochemical samples that met criteria for smoking abstinence, or a Noncontingent group that earned monetary vouchers independent of smoking status (Dunn et al., 2008). Results showed Contingent participants provided significantly more smoking-negative samples than Noncontingent participants (55% vs. 5%, respectively). A second randomized trial that utilized the same 2-week intervention and provided access to the smoking cessation pharmacotherapy bupropion replicated the results of the pilot study (55% and 17% abstinence in Contingent and Noncontingent groups, respectively). A nonsignificant trend suggested bupropion may have contributed to smoking abstinence (Dunn et al, 2010). For both studies high rates of relapse to smoking were observed after the intervention ended; however, the results compare favorably to previous pharmacological and behavioral smoking cessation interventions and provide evidence that opioid-maintained patients can achieve a brief period of continuous smoking abstinence. Relapse to illicit drug use was also evaluated prospectively and no evidence that smoking abstinence was associated with a relapse to illicit drug use was observed (Dunn et al., 2009). It will be important for future studies to evaluate participant characteristics that might predict better treatment outcome, to assess the contribution that pharmacotherapies might have alone or in combination with a CM intervention on smoking cessation and to evaluate methods for maintaining the abstinence that is achieved during this brief intervention for longer periods of time.